Experience of love and interpersonal communication - Zdzisława Marianna Kobylińska (Seminare, 2022)
Interpersonal communication is most fully manifested in the experience of personal love, thanks to which human beings express themselves as loving beings (homo amans). Love has many different dimensions depending on its object. The essence of love can be best grasped at the example of interpersonal relationship between man and woman. Descriptions of love bring to the fore such constitutive factors as selflessness, affirmation, sacrifice, and responsibility. Love has an autonomous and autotelic value, which is why it becomes essential for an authentic act of interpersonal communication.